AKTIVITAS ANTIBAKTERI EKSTRAK DAUN KITOLOD (Isotoma longiflora) TERHADAP PERTUMBUHAN BAKTERI Streptococcus pyogenes - Kartini Kartini; Ari Nuswantoro (LPPM Universitas Abdurrab, 2023)
Kitolod is a plant that is easy to grow in the tropics, including Indonesia. Kitolod leaves contain flavonoids, alkaloids, tannins, saponins and terpenoids that have the potential to be used as antibacterial agents to inhibit the growth of pathogenic bacteria such as Streptococcus pyogenes. This study aims to determine the antibacterial activity of kitolod leaf extract on the growth of Streptococcus pyogenes. This research is quasi-experimental with purposive sampling technique. Kitolod leaves were extracted by maceration method using ethanol then dissolved in 15% DMSO to obtain concentrations of 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, and 90%. Each concentration was replicated three times, and the control used the antibiotic bacitracin. After carrying out the antimicrobial sensitivity test using the Kirby-Bauer diffusion method, the results obtained were inhibition zones of 17.66 mm (sensitive), 18.16 mm (sensitive), 18.50 mm (sensitive), 19 mm (sensitive), 19. 83 mm (sensitive), 21.16 mm (sensitive), 21.83 mm (sensitive), 22.33 mm (sensitive), and 23.83 mm (sensitive) respectively, while the bacitracin control was 17.5 mm (sensitive). Thus, kitolod leaf extract proved to have antibacterial activity against the growth of Streptococcus pyogenes.